The Role of Dark Tourism and its Relationship to Revitalizing International Tourism of Iraq from Specialists' Viewpoint of Tourism Sciences - Asst. Prof. Dr. Radhi Hammoud Jassim (Genius Journals, 2023)
This paper deals with an attempt to define international tourism in general, and then indulging into definition of dark tourism in particular, which is a kind of tourism associated with death and suffering. The term of "dark tourism" has recently appeared in academic field. Therefore, this study is to shed light on concept of dark tourism, its history, and knowing the most important reasons that led to emergence of this type of tourism, as well as standing on the importance of dark tourism in Iraq and its role in increasing human awareness and reasons and motives behind the interest in this tourism, which is termed dark or black, due to its association with some dark and tragic features of humanity such as death, suffering and violence; which is behind transforming battlefields, prisons, and sites of tragedies, holocausts, massacres, and disasters into tourist facades, museums, and attractions for dark tourism, regardless of motive of that, whether it is inclinations, curiosity, or passion. This study attempts to reach a conclusion that international and local governments should take decisions and implement penalties to suppress terrorist actors in the world, as well as it is recommended that families of Speicher martyrs must be cared for, honored financially and morally, and take legal measures against perpetrators
Keywords: Significance of international tourism; dark or black tourism